2016
DOI: 10.1039/c6ra07129e
|View full text |Cite
|
Sign up to set email alerts
|

A study of solvent selectivity on the crystal morphology of FOX-7 via a modified attachment energy model

Abstract: The crystal morphology of FOX-7 in different solvents was investigated via molecular dynamics simulations. A modified attachment energy (MEA) model was constructed by introducing surface chemistry terms and the associated topography of the habit crystal plane. Solvent has a large effect on the crystal morphology of FOX-7. The calculated results show that the crystal morphology of FOX-7 in vacuum is dominated by six faces, (0 1 1), (1 0 À1), (1 0 1), (1 1 À1), (0 0 2) and (1 10), while that in acetic acid is do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The calculations performed provide insights into the stabilizing dimers and intermoleculari nteractions existingi n the crystal systems under study from at hermodynamic point of view.S olvent effects in crystallization may also influence the packing arrangement in co-crystals [59] and is an emerging area of interestinc rystal engineering. Solvent effects and kinetics in the crystallization process couldb ec onsidered separately by using variousm odeling methods such as molecular dynamics, [60] the modified attachment energy model, [61] and lattice Boltzmann methods. [62] Electronic structure perturbations causedb yv arious packing modes were analyzed from the band-structure and density-of-states calculations of selected co-crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations performed provide insights into the stabilizing dimers and intermoleculari nteractions existingi n the crystal systems under study from at hermodynamic point of view.S olvent effects in crystallization may also influence the packing arrangement in co-crystals [59] and is an emerging area of interestinc rystal engineering. Solvent effects and kinetics in the crystallization process couldb ec onsidered separately by using variousm odeling methods such as molecular dynamics, [60] the modified attachment energy model, [61] and lattice Boltzmann methods. [62] Electronic structure perturbations causedb yv arious packing modes were analyzed from the band-structure and density-of-states calculations of selected co-crystals.…”
Section: Introductionmentioning
confidence: 99%
“…3(b), which demonstrates that the stronger the molecular force is, the faster the crystal grows. 10,11 In Fig. 3(b), the blue lines D r a f t represent strong interaction while red lines represent weak interaction, which indicates that FOX-7 grows faster along the blue lines direction than the red lines direction.…”
Section: Fox-7 Crystal Morphology In Vacuummentioning
confidence: 99%
“…Currently, molecular modelling techniques, with low-cost and security, on the prediction of crystal shape have been extensively developed. [9][10][11][12] In particular, the molecular dynamics (MD) simulation which can provide atomic-scale information becomes a powerful one of these techniques. 13 Therefore, the MD simulation method is used to study the dimethyl sulfoxide (DMSO) and temperature effect on the morphology of FOX-7.…”
mentioning
confidence: 99%
“…Figure 3b visualizes the interactions between the catechol molecules calculated and generated by the Crystal Graph in the morphology module, with the blue and red lines representing strong and weak interactions, respectively. Previous studies indicated that crystals grow faster along the direction with strong molecular interactions [44]. Therefore, catechol crystals grow faster along the blue line direction and the surfaces with fast growth rate may disappear, leaving the slowly growing surface appear in the final morphology with six important faces, (1 0 −1), (1 0 1), (0 1 1), (1 1 0), (0 0 2) and (1 1 −1).…”
Section: Prediction Of Catechol Crystal Morphology In Vacuummentioning
confidence: 99%
“…Crystals 2020, 10, x FOR PEER REVIEW 6 of 17 grow faster along the direction with strong molecular interactions [44]. Therefore, catechol crystals grow faster along the blue line direction and the surfaces with fast growth rate may disappear, leaving the slowly growing surface appear in the final morphology with six important faces, (1 0 −1), (1 0 1), (0 1 1), (1 1 0), (0 0 2) and (1 1 −1).…”
Section: Prediction Of Catechol Crystal Morphology In Vacuummentioning
confidence: 99%